Appication of ZO-CRS Stack on Residual PP Removal of PS Component in Converted-Wave Sesimic Reflection Processing - Wahyu Triyoso; Jefri B. Irawan; Natasha C. Viony; Fatkhan Fatkhan (Testing Center for Oil and Gas LEMIGAS, 2020)
A high-quality image of the PS component is needed since applying the converted-wave seismic method has increased significantly in hydrocarbon exploration, especially in interpreting the detail and complexity of structure or reservoir zones. The incident P-wave on a surface produces a reflected and converted P-S wave. Converted-wave seismic uses the multicomponent receiver that records both vertical and horizontal components. The vertical component is assumed to correspond to the compressional PP wave, and the horizontal corresponds to the PS converted-wave. To better understand how to image better the PS component, synthetic seismic data with the shallow gas and relatively complex model are constructed by the full-waveform modeling. This study aims to improve the imaging quality in the PS section to remove the residual PP events on the horizontal data refer to our previous study. In this study, to obtain the more reliable PS data, the residual PP reflections have been removed by applying the Zero Offset Common Reflection Surface (ZO CRS) Stack of the PS component. The results of this study, the imaging quality is better than that in the previous study.